2021
DOI: 10.3389/fpsyg.2021.641729
|View full text |Cite
|
Sign up to set email alerts
|

“Time Slows Down Whenever You Are Around” for Women but Not for Men

Abstract: What happens when we unexpectedly see an attractive potential partner? Previous studies in laboratory settings suggest that the visualization of attractive and unattractive photographs influences the perception of time. The major aim of this research is to study time perception and attraction in a realistic social scenario, by investigating if changes in subjective time measured during a speed dating are associated with attraction. The duration of the dates was variable and participants had to estimate the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 123 publications
0
2
0
Order By: Relevance
“…This raised a question: Would the emotional babyface schema – especially crying – affect men's and women's time perception differently? This is particularly intriguing considering women's pivotal role in childcare, and recent studies have shown a sex difference in time perception (Arantes et al, 2021 ; Glicksohn & Hadad, 2012 ; Tian et al, 2019 ). To investigate this, we designed a second experiment mirroring Experiment 1, but this time focusing on the facial expressions of crying infants and crying adults.…”
Section: Resultsmentioning
confidence: 99%
“…This raised a question: Would the emotional babyface schema – especially crying – affect men's and women's time perception differently? This is particularly intriguing considering women's pivotal role in childcare, and recent studies have shown a sex difference in time perception (Arantes et al, 2021 ; Glicksohn & Hadad, 2012 ; Tian et al, 2019 ). To investigate this, we designed a second experiment mirroring Experiment 1, but this time focusing on the facial expressions of crying infants and crying adults.…”
Section: Resultsmentioning
confidence: 99%
“…In an eclectic paper, Arantes et al manage to link the economic growth of the speed-dating industry to the Angry Birds movie franchise and, at the same time, study how participants allocate cognitive resource to the task of finding a mate. 8 They begin by surveying the literature on attractiveness through an evolutionary lens: perceived attractiveness influences automatic cognitive processes that might confer selective reproductive advantage (for example, if one had to efficiently locate a mate). One such automatic cognitive process is the perception of time – when people are engaged in cognitively demanding tasks, they perceive time as longer than the measured elapsed time.…”
mentioning
confidence: 99%